Relationship between Patient Characteristics and Major Preoperative Anxiety Level at North Aceh Cut Meutia Hospital - Anna Millizia; Hayatul Fitri; Adi Rizka (Faculty of Medicine University of Malikussaleh, 2024)
Introduction: Anxiety in preoperative patients can cause worsening of hemodynamic conditions to complications, in the form of dialysis imbalance syndrome. Preoperative patient anxiety can be influenced by several factors, including patient characteristics. This study aims to determine the relationship between patient characteristics and major preoperative anxiety at Cut Meutia North Aceh Hospital for the September-November 2023 period. Methods: This is observational analytical quantitative research with a cross-sectional design. The total sample in this study was 105 patients with obstetric, gynecological and urological surgery. Sampling in this study uses a purposive sampling technique. The data obtained was analyzed by the Spearman Rank correlation test. Data collection used observation sheets and questionnaires of the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Results: The results of the study showed that the majority of respondents in this study were elderly men (55-90 years old) with marital status and severe poverty category as many as 58 respondents (55.2%). Most respondents with secondary education and an income of < 5 million. The results of the relationship analysis showed that there was a relationship between age and the level of preoperative anxiety with a value of p = 0.038 and a correlation coefficient (r = -0.203) with a negative direction, meaning that the older the patient, the less anxiety the patient would be and vice versa. From the analysis, it was also obtained that there was a relationship between income and pre-operative anxiety with p = 0.028 and a correlation coefficient value (r = -0.214) with a negative direction, meaning that the lower the income, the higher the anxiety experienced by the patient and vice versa. Conclusion: The conclusion of this study shows that there is a relationship between age and income and major preoperative anxiety.